Marketing organizations and cooperative associations for organic farming - Inan H. (The market for organic products in the Mediterranean region, 2003)
In this paper, the basic structures, missions and issues of major marketing organizations and cooperative associations in the USA and EU countries, with reference to organic farming are examined. In this respect, examples from public, private and farm organizations which conduct activities related to organic farming in the World and in Turkey were evaluated. Organic farming organizations and their services are worth looking into in the USA and in most EU countries. On the other hand, such organizations and their affiliated activities on organic farming are rather limited and new in Turkey. In particular, Turkish agricultural cooperatives seem to have made no significant efforts in organic farming at present, probably due to the fact that most of the basic problems of agricultural cooperatives have not been solved. In particular, the issues as the services of cooperatives to organic producers, management of cooperatives to assure producer control and the roles of local, regional and national cooperatives concerning organic farming are of crucial importance to the development of organic cooperatives. The organic food-processing sector in many countries traditionally consists of small and medium sized successful enterprises, which produce one to two speciality products and sell them locally. Large agri-food companies are investing in organic foods and using their names to launch brands available nation-wide. A survey of organic producers whose aim is to explore marketing options may yield important information that will characterize current organic farm production systems, prioritize research needs, guide the development of cooperatives, and stimulate other organic industry initiatives. The survey could include questions related to general organic farm structure, operations and management, and current production constraints. The organic industry provides a unique, and perhaps the last, opportunity to create a more sustainable food and fiber production network, but we must govern our own pricing structures that will allow us to remain on our farms with dignity. A fair return for such an honorable profession is not too much to ask
Intensive Course in: Marketing of Organic Products, 2002/05/20-31, Izmir (Turkey)